An Assessment of Consumer Perception of the Brand Personality of Globacom, Nigeria - Ajeyalemi, Oladipupo Folorunsho; Dixon-Ogbechie, Bolajoko Nkemdillim (Internext, 2020)
Objective: (i) to adapt Aaker’s (1997) scale to measure brand personality in the Nigerian telecommunications market using the methodology identified by Avis (2012) to be the most stable in literature; (ii) to identify the traits that could be used in marketing communication in the telecommunications industry; (iii) to reveal the brand personality factors of the telecommunications industry. Method: The study used a mixed design and survey method to sample 700 consumers of the Nigerian telecommunications industry. Data was collected using a questionnaire and analyzed using inferential statistics. Main Results: Aaker’s (1997) scale was adapted to measure the brand personality in the Nigerian telecommunications industry and it measured six factors, namely, Sincere, Rugged, Sophistication, Competence, Innovative and Excitement.. Relevance/originality: The study provides local empirical evidence of the brand personality factors of the Nigerian telecommunication industry. The scale will be relevant in measuring the brand personality of other brands within the industry. Theoretical/Methodological contributions: The study supported the use of Aaker’s (1997) methodology in developing brand personality scales. The findings were consistent with terminology that could be used to describe brands in the industry. Social Contributions/For management: Managers of Nigerian telecommunication industry brands can make use of the traits identified in marketing communication in order to better present their brands.